Pengaruh Strategi Pembelajaran Everyone Is A Teacher Here (ETH) Terhadap Peningkatan Hasil Dan Motivasi Belajar Kimia Siswa Pada Materi Laju Reaksi - Jeni Tamba; Agus Kembaren (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The low learning outcomes and student learning motivation are influenced by learning activities that are less innovative so that students feel bored and bored. The purpose of this study was to improve student learning outcomes and motivation by implementing the Everyone Is A Teacher Here (ETH) learning strategy. The type of research used is experimental research. The population of this study were all students of class XI IPA at SMA Negeri 1 Dolok Batu Nanggar. A sample of 2 classes was selected using a purposive sampling technique which served as the experimental class and the control class. The data analysis technique used the one-sided t-test, namely the right-hand t-test. The results and discussions that have been carried out show that there is an increase in student learning outcomes and motivation in classes that apply ETH learning strategies, this is evidenced in testing learning outcomes, obtained tcount = 14.3 and ttable = 1.67 (α = 0.05) so that tcount > ttable, then Ha is accepted and the N-gain is 0.71 (high category). Meanwhile, in testing student learning motivation, tcount = 7.95 and ttable = 1.67 (α = 0.05), so tcount > ttable, then Ha is accepted and N-gain is 0.65 (moderate category).